Empowerment, Social Identity, and Language Use: A Case Study of Educated Working Women at the University of Chittagong (Mother Language, 2025)
The empowerment of women is a multifaceted topic that connects with several social, cultural, and political identities. Language, as a medium of communication and expression, significantly influences and reinforces gender identities and power relations. The objective of this research is to investigate the ways in which language can either strengthen or challenge gender stereotypes to create a fair and equitable society. Specifically, a case study of 20 female academics at the University of Chittagong has been conducted through semi-structured interviews and focus group discussions. The results indicate that education, social identities and empowerment visibly influence the language use of highly educated working women. This research underscores the pivotal role of women’s empowerment in shaping their social identity and its impact on linguistic expression within the societal context. This research on women’s empowerment in language use has ultimately revealed the importance of linguistic practices as both reflective of and instrumental in shaping social power activities.Mother Language 2024; 8(1-2): 27-48